2009
DOI: 10.1177/104063870902100607
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin and Vimentin Co-Expression in 21 Canine Primary Pulmonary Epithelial Neoplasms

Abstract: Co-expression of cytokeratin and vimentin has been traditionally associated with a few select tumors. However, this phenomenon is being recognized in a wider range of tumors. Twenty-one canine primary pulmonary epithelial neoplasms were evaluated for the co-expression of cytokeratin and vimentin. The histologic pattern and grade, and an immunohistochemical grade for cytokeratin and vimentin staining, were determined for each neoplasm. Adenocarcinomas predominated, and histologically, most tumors were grade II.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
9
1
5
Order By: Relevance
“…Moreover, co-expression of cytokeratin and vimentin has also been found in tumors which, in cases of dissemination, can be included in differential diagnosis of visceral tumors, among them thyroid carcinomas, prostatic carcinomas, endometrial adenocarcinoma, ovarian epithelial tumors and mammary gland carcinomas (Grieco et al 2003, Riccardi et al 2007, Pires et al 2010. The study performed on the canine lung carcinomas has revealed co-expression of cytokeratin and vimentin in neoplastic cells in 38% of cases (Burgess and Kerr 2009). Additionally, cancers with more anaplastic appearance showed vimentin immunoreactivity more often than in moderate or well differentiated types of cancers (Burgess and Kerr 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, co-expression of cytokeratin and vimentin has also been found in tumors which, in cases of dissemination, can be included in differential diagnosis of visceral tumors, among them thyroid carcinomas, prostatic carcinomas, endometrial adenocarcinoma, ovarian epithelial tumors and mammary gland carcinomas (Grieco et al 2003, Riccardi et al 2007, Pires et al 2010. The study performed on the canine lung carcinomas has revealed co-expression of cytokeratin and vimentin in neoplastic cells in 38% of cases (Burgess and Kerr 2009). Additionally, cancers with more anaplastic appearance showed vimentin immunoreactivity more often than in moderate or well differentiated types of cancers (Burgess and Kerr 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The study performed on the canine lung carcinomas has revealed co-expression of cytokeratin and vimentin in neoplastic cells in 38% of cases (Burgess and Kerr 2009). Additionally, cancers with more anaplastic appearance showed vimentin immunoreactivity more often than in moderate or well differentiated types of cancers (Burgess and Kerr 2009). Moreover, vimentin immunoreactivity in the prostatic carcinomas in both humans and dogs was considered to be associated with more invasive phenotype and thus typical for more disseminated forms of cancer (Grieco et al 2003, Ricardi et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical (IHC) assays were performed on 1 lung tumor using murine monoclonal antibodies against cytokeratin (AE1/AE3; Sigma-Aldrich, Oakville, Canada) and vimentin (BioGenex, Fremont, CA) at 1:200 and 1:100 dilutions, respectively. 5 Samples or sterile swabs of all grossly observed purulent lesions underwent routine aerobic and anaerobic bacterial isolation and identification.…”
Section: Histopathologymentioning
confidence: 99%
“…As neoplasias pulmonares de origem epitelial ainda devem ser diferenciadas quanto à malignidade e tipo histológico (Wilson e Dungworth, 2002). O adenocarcinoma pulmonar do tipo acinar apresenta diversos padrões histológicos (Burgess e Kerr, 2009). Geralmente localiza-se no tecido pulmonar periférico e dissemina-se em vários outros nódulos (Wilson e Dungworth, 2002) ou ocorre na forma de massas sólidas, brancacentas e multifocais .…”
Section: Adenocarcinoma Acinar Pulmonar Em Um Cão -Relato De Casounclassified